2015
DOI: 10.1017/s1049023x15004951
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Injuries and Their Treatment in Children During Earthquakes: A Systematic Review

Abstract: Orthopedic injuries commonly affect children during earthquakes, but reports about them are rare. This setting may lead to different standards of care, but guidelines are still missing in this field. A systematic review was performed to: (1) assess type and body distribution of pediatric earthquake-related injuries, treatment performed, length of stay, and complications; and (2) identify starting points to define standards of care. PubMed database was researched for papers (1999-2014 period) in agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 27 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…Although primary data on the anatomic locations of orthopaedic extremity injuries exist for individual major earthquakes, no review has compiled detailed epidemiologic data from these studies. Several reviews have more broadly characterized injury patterns as “lower limb” or “upper limb” and “open” or “closed” [ 5 , 6 ] but do not contain more detailed epidemiologic information.…”
Section: Introductionmentioning
confidence: 99%
“…Although primary data on the anatomic locations of orthopaedic extremity injuries exist for individual major earthquakes, no review has compiled detailed epidemiologic data from these studies. Several reviews have more broadly characterized injury patterns as “lower limb” or “upper limb” and “open” or “closed” [ 5 , 6 ] but do not contain more detailed epidemiologic information.…”
Section: Introductionmentioning
confidence: 99%
“…However, retrospective event data, particularly in disaster medicine, are the norm. It is suggested that every systematic review faces challenges in terms of the quality of data collected 64 . There was also a geographical and publication bias with 20 of the 60 studies conducted in the US.…”
Section: Limitationsmentioning
confidence: 99%
“…The majority of the data used in this study were retrospective, eventbased data which can be considered to jeopardize the scientific quality and validity of findings. 64 However, retrospective event data, particularly in disaster medicine, are the norm. It is suggested that every systematic review faces challenges in terms of the quality of data collected.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…shows the 58 articles that were entered into the final SLR study, with 46 single studies, 11 multiple studies, and 21 with control groups. There was 1 study determined to be LOE 18, 29 LOE 2 9-37 , and 28 LOE 3 , with 15 determined to achieve QE 18,11,14,16,18,24,25,31,43,44,46,48,50,55,63,65 , 37 QE 29,10,12,13,15,17,19,21,[26][27][28][29][30][32][33][34][35][36][37][38][39][40][41][42]47,49,51,52,[56][57][58][59][60][61]…”
mentioning
confidence: 99%